2016
DOI: 10.1111/jvim.14527
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent At‐Home Suctioning of Esophageal Content for Prevention of Recurrent Aspiration Pneumonia in 4 Dogs with Megaesophagus

Abstract: BackgroundMegaesophagus carries a poor to guarded prognosis due to death from aspiration pneumonia. Options for medical management of regurgitation are limited to strategic oral or gastrostomy tube feeding.ObjectivesTo describe the use and efficacy of intermittent esophageal suctioning to prevent regurgitation and associated episodes of aspiration pneumonia in dogs with megaesophagus.AnimalsFour dogs with acquired idiopathic megaesophagus and recurrent aspiration pneumonia.MethodsRetrospective review of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Depending on the cause, ME is classified into primary ME, which is idiopathic, or secondary ME, which occurs in conjunction with other diseases including myasthenia gravis, hypoadrenocorticism, dysautonomia, polyradiculoneuritis, hypothyroidism, polymyopathies and esophageal cancer [ 1 , 2 , 4 , 6 , 9 , 10 , 11 , 15 ]. A recent study reported that most cases of canine ME were idiopathic (IME) (76%), and the rest were secondary ME (24%), mainly involving myasthenia gravis [ 7 ]. While the treatment for secondary ME is dependent on the underlying disease, there is no curative treatment for IME.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on the cause, ME is classified into primary ME, which is idiopathic, or secondary ME, which occurs in conjunction with other diseases including myasthenia gravis, hypoadrenocorticism, dysautonomia, polyradiculoneuritis, hypothyroidism, polymyopathies and esophageal cancer [ 1 , 2 , 4 , 6 , 9 , 10 , 11 , 15 ]. A recent study reported that most cases of canine ME were idiopathic (IME) (76%), and the rest were secondary ME (24%), mainly involving myasthenia gravis [ 7 ]. While the treatment for secondary ME is dependent on the underlying disease, there is no curative treatment for IME.…”
mentioning
confidence: 99%
“…However, patients with severe ME may develop weight loss, weakness and often complicated aspiration pneumonia (AP) [ 3 , 5 ]. The prognosis of ME is poor, and the median survival time has been reported to be 90 days in dogs [ 7 ]. The prognosis is especially poor in ME with complicating AP, and their median survival time is reported as 16 days [ 7 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Survey radiographs revealed gasfilled and overdistended esophagus and no evidence of pneumonia (Figure 1A and B). Based on a history of regurgitation and the identification of esophageal dilation on survey radiographs without chemical restraint (Manning et al, 2016), thus megaesophagus (ME) was diagnosed. For identifying comorbidities or concurrent diseases which could be a primary cause of ME, the diagnostic evaluations included blood analyses including complete blood counts, serum biochemistry and electrolytes, echocardiography, thyroid profiling, adrenocorticotropic hormone (ACTH) stimulation test, and an acetylcholine receptor antibody tittering.…”
Section: Case Historymentioning
confidence: 99%